Determinants of Enterprise restructuring in Transition: Description of a Survey in Russian Industry - Luc Moers (Tinbergen Institute, 2000)
To achieve sustainable economic growth in transition countries, it is crucial that enterpriseperformance is improved. However, it is not a priori clear which factors are essential for this. ForRussia, data to investigate the potential determinants of enterprise performance is scarce.Therefore, the survey described in this paper collects data on enterprise restructuring, ownership,competition, budget constraints and, particularly, institutions in Russian industry, covering theperiod between the start of 1992 and September 1999. On their own, the survey answers show adevastating restructuring crisis, massive privatization, rather weak competition, unexpectedly hardbudget constraints, an overwhelmingly negative and relatively positive assessment of formal andinformal institutions respectively, and largely the same ruling networks as before the start of marketreforms. Ironically, tentative results based on this survey indicate that (un)important determinantsof enterprise restructuring in Russian industry are exactly those on which, according to the responseper se, least (most) reform has been accomplished. That is: stronger competition and betterinstitutions go with more restructuring, while privatization and harder budget constraints do not.The substitution, to some extent, of informal for formal institutions may have prevented even worserestructuring figures, but the results also suggest that better formal institutions in general wouldhave led to further improvements.
Keywords: D21; O12; P21; P27; P31; 330; Transition economics; Russia; enterprise restructuring; policy reform; institutions; Systemtransformation; Organisatorischer Wandel; Industrie; Russland